(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Wider Zagreb city area, capital city of Republic of Croatia, has significant potential for major implementation of geothermal heat pump systems in not just the residential sector, but in commercial sector as well. Geothermal heat pumps often cumulatively describes different earth energy heat exchanger installations, from groundwater up to shallow ground horizontal and borehole heat exchangers installations. Zagreb area has especially favourable both hydrogeological and thermogeological parameters, which allows implementation of different designs for residential and commercial heating and cooling. Analysis of comparative energy and economy advantages of heating and cooling with heat pump systems (air, ground or groundwater) was made for capital city of Zagreb. Since heat pump systems in residential area is always higher-class investment, there is often a need for whole year heating since projects increasingly incorporate outside swimming pool. Up till now, many authors investigated comparison of winter heating energy cost for different heat pump systems. However, outdoor swimming pool sometimes consumes as much heating energy during spring-summer-autumn season, as do house in autumn-winter-spring season. Since air temperatures during spring-summer season are much more favourable then sub-cooled ground or groundwater temperatures, air-source heat pumps when used in whole year round for heating, could offset economically unfavourable coefficient of performance (COP) during coldest days of winter. On a real residential home, currently in construction phase, techno-economic analysis was performed comparing seasonal performance factor (SPF) for different heat pump systems during whole year round heating.